Establishing a translational genomics infrastructure in pediatric cancer: the GREAT KIDS experience. (June 2015) - Pinto, Navin; Volchenboum, Samuel L; Skol, Andrew D; Rhodes, Lindsay; Doan, Andrew; Fein-Levy, Carolyn; Lipton, Jeffrey M; Cunningham, John M; Onel, Kenan
We have recently established a biobanking and sequencing pipeline at the University of Chicago dubbed Genomics for Risk Evaluation and Anticancer Therapy in Kids. We plan to intersect family and personal history of cancer and other diseases with multidimensional genomic profiling in order to: understand how genetics may have contributed to the development of cancer for each child, and investigate the spectrum of genomic alterations within a tumor spatially (e.g., primary site vs distant metastasis) and over time (e.g., diagnosis vs relapse). This review highlights some of the practical considerations involved in creating such a program including the capacity to use our platform for multi-institutional collaborations.